Adaptive optics enables three-dimensional single particle tracking at the sub-millisecond scale - Juette, Manuel Friedrich; Rivera-Molina, Felix E.; Toomre, Derek K.; Bewersdorf, Joerg (Applied physics letters, 2013)
We present the integration of an adaptive optics element into a feedback-driven single particle tracking microscope. Our instrument captures three-dimensional (3D) trajectories with down to 130 μs temporal resolution for dynamic studies on the nanoscale. Our 3D beam steering approach tracks particles over an axial range of >6 μm with ∼2 ms mechanical response times and isolates the sample from any tracking motion. Tracking of transport vesicles containing Alexa488-labeled transferrin glycoprotein in living cells demonstrates the speed and sensitivity of our instrument.
Gesehen am 09.04.2021